Comparative study of the outcome and early complications between stapled and open hemorrhoidectomy - Manzoor, Shahzada Faisal; Bhat, Sandeep; Zargar, Owais-Ul-Umer; Riaz, Mohd. (International Journal of Research in Medical Sciences, 2025)
Background: Hemorrhoids also known as piles are vascular cushions in the anal canal that help with stool control. When these cushions are swollen or inflamed, they become a disease. The signs and symptoms depend on the type present. Internal hemorrhoids often result in painless, bright red rectal bleeding while defecating whereas external hemorrhoids mostly present with pain and swelling in the area of the anus. Methods: This study was conducted in the department of surgery, GMC Jammu during the time period of one year. After seeking consent to be a part of study, patients were subject to either of the procedures based on their allotted groups and aim was to compare the outcome and early complications between stapled and open hemorrhoidectomy groups. Results: A total of 90 patients were taken for the study and 45 patients were recruited to each group. VAS (visual analog scale) scores for pain were better in the stapled group. None of the stapled patients complained of bleeding beyond first post-op week. In the open group 1 patient continued to complain of bleeding during defaecation even at 45 days. The mean hospital stay was lower and return to work was earlier in stappled group as compared to open group. The incidence of postoperative fever, incontinence to flatus, urinary retention, mucus discharge, unhealed anal wound, anal stenosis and recurrence was more in the open group as compared to stappled group. Conclusions: Our study affirms stapled hemorrhoidectomy as a superior procedure in terms of early outcomes, with lesser post-op pain and bleeding, early hospital discharge, early return to work, less complications and low recurrence rate as compared to open hemorrhoidectomy.